El razonamiento lógico-matemático en el proceso de enseñanza-aprendizaje en los estudiantes de Educación Básica Superior en la escuela Gabriel Urbina. - Tubón Escobar, Fernando Javier (2020)
Logical-mathematical reasoning in the teaching-learning process is an initial and priority component for the development of critical and reflexive thinking of the individual within a socio-educational context. Therefore, it analyzed the incidence of the teaching-learning process, in the development of mathematical logical reasoning, in students of Higher Basic General Education. The research was supported by an informative and scientific literature review from an exploratory, diagnostic and descriptive approach. For this purpose, the diagnosis and application of instruments and techniques, such as the interview and survey, was carried out to gather information in reference to the problem statement. The diagnosis and application of the instruments describe the need to improve logical-mathematical reasoning in the teaching-learning process through a proposal focused on workshops of methodological strategies. Procedure began with the perceptual level, which allowed exploring and describing everything that is defined about the logical-mathematical reasoning in the teaching-learning process, taking into account students’ needs. The results show that 90% (18 students) achieved a significant improvement in the development of the logical mathematical reasoning compared with those in a moderate range (10%). The results indicate that the proposal "strategies to develop reasoning logical-mathematical" contributed significantly to the process of teaching and learning, that is, its application and continuity and feasible. It is hoped that the results of this research contribute to the disciplinary field to teaching mathematics, be taken as a reference to improve this process, and the guideline for future research